PREEMPTIVE KETAMINE FOR POSTOPERATIVE ANALGESIA FOLLOWING GENERAL ANESTHESIA-ASSISTED TOTAL ABDOMINAL HYSTERECTOMY (TAH) - Fazal Wadood; Shahid Maqsood; Mohammad Javed; Umbrin Naz; Abid Iqbal; Osama Farooq (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: The best way to deal with pain after surgery is to start treating it before it even happens, according to the theory of "pre-emptive analgesia." Postoperative pain following total abdominal hysterectomy can be effectively managed with preemptive low-dose Ketamine. Objectives: This study set out to answer whether or not prophylactic low-dose Ketamine can be used to effectively treat acute postoperative pain in patients who had undergone general anesthesia for a total abdominal hysterectomy. Study Setting: Khyber Teaching Hospital, Peshawar from January 2023 to June 2023. Methods: Fifty-two women between the ages of 35 and 50 who hadcomplete elective Patients undergoing general anesthesia for abdominal hysterectomy were randomly divided into two groups, those with ASA physical status I and those with ASA physical status II. Group A patients were given a 60-90 second I/V infusion of 10 ml of normal saline before surgical incision. Within 60-90 seconds before incision, patients in Group B received 0.15 mg/kg ketamine (in 10 ml normal saline) I/V. Consistent anesthetic procedures and patient interviews became the norm. Information on pain, analgesic use, adverse events, and the degree of recovery was collected over 24 hours. Results: Patients who were given Ketamine before surgery reported much less pain in the first 24 hours after the procedure than those who were given a placebo. First, analgesic requirements were significantly lower in group A (25.67±1.60) than in group B (57.3±32.97; p = 0.00). Opioid use was significantly higher in group A (290.00±9.09) than in group B (210.6±77.01) (p = 0.00). The urgency with which analgesia was required and the total amount utilized differed significantly between the groups. Neither group differed significantly from the other regarding hemodynamic variables or adverse effects. Conclusion: Avoidance therapy with a low dose of intravenousKetamine is well-tolerated, non-opioid analgesia effective in coping with moderate-to-severe discomfort after surgery.